An error analysis of verbs used by Bidayuh ESL students / Ahdis Jamut - Jamut, Ahdis (2008)
This study reveals the verb errors made by Form 4 and 5 Science Bidayuh students in Bau district. Two instruments; argumentative essays and Learner Profile were utilized to identify the verb errors committed by the students and their relationship to the learners' variables such as gender differences, place of origin, English tuition attended and the languages spoken. The study has collected 34510 words of learners writing in the form of argumentative essays with the topic "Life today is better than ten years ago". The study follows the methodological principles laid down by Corder (1974). The data was analysed using a computerized error-tagging programme known as the VCL Error Editor (Dagneaux: et al, 1996). The programme comprised a wide range of error tags inserted manually, and allowed the researcher to identify and classify the errors produced by the students in their essays. Next, the tagged texts were processed by the WordSmith Tools Concordance Programme, to obtain error frequencies arranged by gender and error category. The errors were then cross-tabulated and correlated using SPSS to investigate significant relationships between background variables and the verb errors committed. A number of observations were made concerning the causes of errors produced by the students. The findings of the study reveal that verb tense errors (tagged GVT) were the most frequent errors made in the corpus samples. The study also indicates no significant relationship between the learners' variables with the type of verb errors made by the students. The major causes of errors are over-generalization, incomplete application of rule, and L1 interference. The implications of the study include the needs for teachers to provide constructive feedback with regard to the erroneous language items made by the students to prevent fossilization. Teachers should adopt and adapt new methods of teaching and utilize materials which maximize the strengths and minimize the weaknesses of their ESL learners. An explicit teaching of basic grammar to the students is essential so as to raise consciousness to the correct and incorrect forms of the language. Suggestions for further research include carrying out similar research over a long period of time, an experimental research on the explicit teaching of grammar in the classroom, a study on the influence of L1 inference on ESL learners, the effect of multilingualism on ESL learners and a comparative study of errors made by ESL learners from different racial backgrounds.